Sanksi Hukum terhadap Anggota Polisi yang Melakukan Tindak Pidana Pembunuhan - Ni Komang Ayu Sri Agustini; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2021)
The police are essentially government institutions and functions that are engaged in maintaining public security and order. The number of temptations causes the police to commit violations or criminal acts. This study aims to understand the legal arrangements against police officers who commit crimes and examine legal sanctions and legal rules that regulate problems in legal arrangements against police officers who commit criminal acts and forms of legal sanctions against the crime of murder. The research method uses normative legal research with a statutory and conceptual approach. Sources of legal materials consist of primary legal materials and secondary data. Data collection is done by reading the law on the police. Data analysis was carried out by case studies namely; the legal materials obtained in the research were processed and analyzed, and presented in a descriptive-analytical manner. The results of the study indicated that legal arrangements for police officers who commit murder crimes, where violations of the code of ethics have consequences, will be tried by the commission of the professional code of ethics. The legal sanction is that a police officer who commits a crime will be processed through a general court trial, undergo sanctions, and undergo a code of ethics trial with dishonorable dismissal. The imposition of disciplinary sanctions is decided in a disciplinary hearing for members of the police who violate police discipline and code of ethics